Arthroscopic (Arthro) Delivery of MACI (Autologous Cultured Chondrocytes on a Porcine Collagen Membrane) for Defects on Condyles - Michael A. Kuhn MD (Video Journal of Sports Medicine, 2025)
Background: Knee femoral chondral pathology is frequently encountered during knee arthroscopies. Based on previous studies, the unaddressed, painful, poor knee function progresses into arthritis. Addressing this scenario with a simple, less invasive arthroscopic procedure may provide a simple solution for this cohort of patients. Indications: The arthroscopic autologous cultured chondrocytes on a porcine collagen membrane (matrix-induced autologous chondrocyte implantation [MACI]) procedure is indicated when chondral lesions are located on the femoral condyles, with symptoms consistent with the location that corresponds to magnetic resonance imaging findings between 2 and 4 cm 2 , contained with a stable rim, and grade 3 to 4a International Cartilage Repair Society defects. Technique Description: This novel technique for arthroscopic delivery of MACI for defects on femoral condyles was developed as the next step in the evolution of the autologous chondrocyte implantation technology. The technique describes the newly developed instruments—a unique measuring probe, 3 types of curettes, the arthroscopic and MACI membrane cutters, and the V-shuttle delivery device. Also, attention is paid to the medial and lateral approach, defect preparation, fluid control, implant and fibrin sealant delivery, and simple closure. Arthroscopic surgical procedures typically result in less pain after surgery, requiring fewer pain medications, earlier and improved range of motion/function, less postoperative muscle weakness, and faster recovery, and for patients concerned about cosmesis, arthroscopic joint repair may reduce scarring. Discussed are the special differences between open and arthroscopic delivery of MACI, summarizing the pros and cons. Results: Compared to many other knee ligament or meniscus arthroscopic procedures, the addition of arthroscopic delivery of MACI for defects on knee femoral condyles is appealing and easy to implement by an experienced surgeon. The development of instruments simplified the procedure and elevated it to an art form. Discussion/Conclusion: Chondral lesions of the femoral condyles of the knee can effectively be treated with the arthroscopic MACI technique. Potential benefits include minimal surgery disruption, concomitant knee arthroscopic procedures, cosmetic appeal, improved quality of life, and level of function. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.